Prof. Dr. Valentina Serreli and Prof. Dr. Elshifa Elamin on the colonial language rights regime in Sudan - Serreli, Valentina; Elamin, Elshifa (Cluster Conversations, 2024)
This latest episode features Prof. Dr. Valentina Serreli talking with Cluster fellow Dr. Elshifa Elamin about her research project in which she scrutinizes the language rights regime in Sudan enforced by the British colonial system.